Parallel numerical computation of mixed convection in a square enclosure with multiple heat sources on Anucluster: Mixed convection in a square cavity - Kumar, B. V. Rathish; Nigam, Mohit; Kumari, Priti; Sharma, Parul (International journal of advances in engineering sciences and applied mathematics, 2015)
The coupled nonlinear partial differential equations modelling the influence of multiple heat sources on the mixed convection process in a fluid saturated vertical porous square enclosure have been solved numerically by Galerkin finite element method in conjuction with the Krylov Solver BICGM. Detailed parallel numerical computations, based on the message passing libraries from ANULIB, have been carried out on an eight noded ANUCLUSTER to assess the influence of flow governing paremeters such as Rayleigh number and suction/injection velocity on mixed convection process. The obtained results have been analysed for heat and mass transfer in the form of isotherm, streamline and velocity vector plots. Local, cumulative and global heat fluxes have been calculated in the form of corresponding versions of Nusselt number. Computations have also been carried out for the case natural convection due the multiple hot sources. Nusselt numbers from mixed convection process are compared with those from natural convection process. Efficiency and speedup of the parallel computations on ANUCLUSTER have also been assessed and presented.